ANALISIS KINERJA PEMERINTAH KECAMATAN DALAM MEMBERIKAN PELAYANAN PUBLIK TERHADAP MASYARAKAT DI KECAMATAN RAPPOCINI KOTA MAKASSAR - Harbiyanto, Alfian (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
To find out the implementation of public service tasks in the Makassar City district of Rappocini; 2) To find out how the performance of the Rappocini sub-district government of Makassar city in providing public services to the public; 3) To find out what factors support and hinder the performance of the Makassar city Rappocini sub-district government officials in providing public services to the community. The research method used is to use a descriptive research method. The population in this study amounted to 140 people and the sample in this study amounted to 65 respondents. Data collection techniques used were interviews, observation, literature. Data analysis techniques were descriptive qualitative. The results of this study indicate that the performance of the Rappocini sub-district government in providing public services in the Rappocini sub-district of Makassar City is generally good. While the factors that support and hinder the performance of the Rappocini Subdistrict government in providing public services to the community are the professionalism factor of the apparatus, the factor of public awareness, the regulatory factor and the service facility and infrastructure factor.